Treatment with proton pump inhibitors is associated with increased mortality in patients with pyogenic liver abscess. Issue 6 (12th January 2018) - Bettinger, D.; Martin, D.; Rieg, S.; Schultheiss, M.; Buettner, N.; Thimme, R.; Boettler, T.
Summary: Background: Proton pump inhibitors (PPI) are often used in patients with gastro‐esophageal reflux and peptic ulcer disease. A higher risk for infectious diseases and for pyogenic liver abscess has been reported in patients with prolonged PPI intake. Although many patients have ongoing PPI treatment after diagnosis of liver abscess, there are no data available that focus on the prognostic impact of PPI treatment in these patients. Aim: To analyse the effect of PPI treatment on mortality in patients with pyogenic liver abscesses. Methods: Between January 2005 and March 2017, one hundred and eighty‐one patients with pyogenic liver abscess were retrospectively included in this analysis. Medical records including PPI treatment, microbiological and imaging data were reviewed. The primary endpoint was index mortality and predictive factors were analysed using uni‐ and multivariate logistic regression models. Results: One hundred patients with pyogenic liver abscess (55.2%) were treated with PPI compared to 81 patients (44.8%) without PPI treatment. In both patient cohorts, enterococcus spp. and streptococcus of the anginous group were the most common pathogens identified. Patients with PPI treatment had significantly higher index mortality compared to patients without PPI treatment (30.0% vs 11.1%, P = 0.003). After adjusting for comorbidities PPI remained an independent predictive factor with an OR of 2.56 (1.01‐6.46, P = 0.036). Conclusions: PPI treatment is associated with higher index mortality in patients with pyogenic liver abscess. Therefore, critical evaluation of the indication for PPI treatment is particularly important in patients at high risk for pyogenic liver abscess. Abstract : Linked Content This article is linked to Tabibian and Lindor and Bettinger et al papers. To view these articles visit visit https://doi.org/10.1111/apt.14568 and https://doi.org/10.1111/apt.14591 .